PENGARUH KEHIDUPAN ROHANI UMAT PAROKI TERHADAP MINAT SISWA KOTA RUTENG DALAM MENDALAMI KITAB SUCI - Yosef Masan Toron; Keristian Dahurandi; Hironinus Bandur; Oswaldus Bule; Marselus Ruben Payong; Hendrikus Midun (Lembaga Penelitian STKIP Widya Yuwana, 2022)
This study aims to describe the influence of the parish spiritual life toward students' interest in studying the Bible. This study used a quantitative approach. The research sample consisted of 332 high school students, both private and public, in the city of Ruteng, Manggarai Regency, which were taken using a proportional random technique. The data collection instrument used a closed questionnaire. The data analysis technique used Pearson Product Moment Correlation with SPSS version 23.0. The results of the data analysis showed that there was a correlation between parish spiritual life and an interest in studying the scriptures (r = 0.605). As a result, the parish spiritual life contributes 36.4% to the interest in studying the scriptures. Since the regression of biblical interest in parish spiritual life is linear, this relationship is predictable. So, more involvement in spiritual life in the parish means that students will be more interested in studying the scriptures if they spend more time there.